Designing potential siRNA molecule for the nucleocapsid(N) gene silencing of different SARS-CoV-2 strains of Bangladesh: Computational approach. (June 2021) - Bappy, Syed Shahariar; Shibly, Abu Zaffar; Sultana, Sorna; Mohiuddin, A.K.M.; Kabir, Yearul
Graphical abstract: Abstract: SARS-CoV-2 is a single-stranded RNA (+) virus first identified in China and then became an ongoing global outbreak. In most cases, it is fatal in humans due to respiratory malfunction. Extensive researches are going to find an effective therapeutic technique for the treatment of SARS-CoV-2 infected individuals. In this study, we attempted to design a siRNA molecule to silence the most suitable nucleocapsid( N ) gene of SARS-CoV-2, which play a major role during viral pathogenesis, replication, encapsidation and RNA packaging. At first, 270 complete N gene sequences of different strains in Bangladesh of these viruses were retrieved from the NCBI database. Different computational methods were used to design siRNA molecules. A siRNA molecule was built against these strains using the SiDirect 2.0 server. Using Mfold and the OligoCalc server, the siRNA molecule was tested for its secondary structure and GC material. The Clustal Omega tool was employed to evaluate any off-target harmony of the planned siRNA molecule. Herein, we proposed a duplex siRNA molecule that does not fit any off-target sequences for the gene silencing of SARS-CoV-2. To treat SARS-CoV-2 infections, currently, any effective therapy is not available. Our engineered siRNA molecule could give an alternative therapeutic approach against various sequenced SARS-CoV-2 strains in Bangladesh.